Application of boundary electro-osmotic pulse to reduce sludge-to-wall adhesion. (1st May 2021) - Deng, Wenyi; Zhou, Jie; Yu, Li; Pan, Sirui; Xiao, Jiamin; Lai, Zhichen; Su, Yaxin
Highlights: Sludge adhesion decreased by 24.4%-54.4% under the effect of BEOP. Adhesion reduction mainly attributed to the formation of water layer on cathode by BEOP. Sludge with lower moisture content had a better adhesion reduction through BEOP. Current on the cathode surface decayed quickly with the increase of distance way from anode. Abstract: Adhesion is one of the main features of sewage sludge. This paper aims at reducing sludge-to-wall adhesion through formation of a water layer induced by boundary electro-osmotic pulse (BEOP) which is characterized by distributing anodes and cathodes on one surface and exerting a pulsating current. The effects of the related parameters, including current intensity, exerting time, frequency, duty cycle (DTC), and the ratio of cathodic surface area to anodic surface area (C/A), on the adhesive stress of sewage sludge with different moisture content were thoroughly studied. The results indicated that, under the optimal conditions of BEOP, the adhesive stress of sludge with moisture content of 35%, 45%, 60% and 70% was reduced by 40.4%, 54.5%, 31%, and 24.4%, respectively. The migrations of water, ions and organic matters were also investigated to explore the functional mechanism of BEOP. The results showed that the water migrated from the anode side to the cathode side, whereas the organic matters migrated in the opposite direction. The increment of the sludge moisture content on the cathode surface was reduced with the increase of distance away from the anode. Based on theoretical modeling, the distributions of current density and temperature in sludge cake were obtained. The current flowed from anode to cathode and decayed quickly with the increase of the flowing distance, which well explained the moisture content distribution in sludge cake. Graphical abstract: Image, graphical abstract